Long-Term Coastal Evolution Based on Comparison of Inferred Paleo Shoreline and Present Shoreline Along the Mahanadi Tri-Delta Coast, Eastern India. - Rajan Boopathy,; Yoganandan Veeran,; Roop Singh Kankara, (The Bioscan, 2026)
Over the millions of years, the Mahanadi delta prograded and marched towards sea with the evolution of various coastal units such as older deltaic plains, younger deltaic plains, older coastal plains and younger coastal plains and their various landforms. Annually, the Mahanadi River contributes a significant amount of sediment to the coastal environment, discharging approximately 49.0 ± 20.5 km³ of water and 17.4 ± 12.7 × 10⁶ tons of sediment into the Bay of Bengal.Specifically, it helps to understand the rate of delta growth and coastal migration towards sea over the time scale. And by comparing the former and the present position helps to understand the sediment redistribution and coastal evolutions and their patterns.In light of this, the study aims to reconstruct the paleo shoreline position and analyse with the present shoreline position and to compare the long-term coastal evolution along the study area. The inferred paleo shoreline covers a distance of 157.74 km along the inland parallel to the coast. The results show that the paleo shoreline has been displaced up to 80 km towards sea and the combined prograded landform area meets 7494.67 sq km. For understanding the long-term shoreline change trend, the study uses the 59 years dataset from 1965 to 2024. Using Digital Shoreline Analysis System (DSAS), shoreline change analysis were performed with 3452 transects along 71 km.Over the 59 years, the result shows that southern sector is dominated by the accretion with local erosion, the central sector is redistributed between erosion and accretion and the northern sector is dominated by the continuous erosion. The overall behaviour of the modern sectors clearly shows that the coast is not continuously receiving the sediment from river source which results in localized erosion and accretion and hence it is not uniformly prograding in recent years compared to past delta progradation.